2013
DOI: 10.1103/physreva.87.032509
|View full text |Cite
|
Sign up to set email alerts
|

Energies and the radiative and Auger transition rates of1s2p4resonances of B-like ions

Abstract: Energy levels and the radiative and Auger transition rates of the 1s2p 4 2,4 L (L = S, P , D) resonances in the boron isoelectronic sequence are calculated using the saddle-point variation and saddle-point complex-rotation methods. Large-scale wave functions are used to saturate the functional space. Relativistic and mass polarization corrections are included by the first-order perturbation theory. The Auger branching ratios of the important decay channels for these core-excited states are calculated. The reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 23 publications
7
13
0
Order By: Relevance
“…Sun and co-workers [30] used the SPM with rotation to calculate energy levels and Auger decay widths for the 1s2s 2 2p 2 and 1s2s2p 3 2,4 L levels in B-like carbon and found suitable agreement with the re-calibrated spectrum of Bruch and co-workers [31] and the combined theoretical work and high resolution synchrotron measurements performed at the ALS [32]. In the case of O 3+ ions, recent saddle-point with rotation calculations by Sun and co-workers [33] for the energy levels and Auger and radiative decay rates for the 1s2s 2 2p 2 and 1s2s2p 3 2,4 L levels were compared to the earlier beam-foil experimental measurements of Bruch and co-workers [11], the MCDF work of Chen and Craseman [23,24] and further extended to the higher lying 1s2p 4 levels of other B-like ions [34].…”
Section: Introductionmentioning
confidence: 99%
“…Sun and co-workers [30] used the SPM with rotation to calculate energy levels and Auger decay widths for the 1s2s 2 2p 2 and 1s2s2p 3 2,4 L levels in B-like carbon and found suitable agreement with the re-calibrated spectrum of Bruch and co-workers [31] and the combined theoretical work and high resolution synchrotron measurements performed at the ALS [32]. In the case of O 3+ ions, recent saddle-point with rotation calculations by Sun and co-workers [33] for the energy levels and Auger and radiative decay rates for the 1s2s 2 2p 2 and 1s2s2p 3 2,4 L levels were compared to the earlier beam-foil experimental measurements of Bruch and co-workers [11], the MCDF work of Chen and Craseman [23,24] and further extended to the higher lying 1s2p 4 levels of other B-like ions [34].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, earlier work by Chen et al (1997Chen et al ( , 1988Chen et al ( , 1987 investigated the K-shell Auger decay and radiative transitions for the carbon-like and boron-like ions including O 2+ and O 3+ using the multi-configuration DiracFock (MCDF) approach. For O 3+ , additional variety of methods such as 1/Z perturbation theory (Safronova & Shlyaptseva 1999) and the saddle-point-method with R-matrix, complex coordinate rotation methods (Chung 1990;Lin et al 2001Lin et al , 2002Sun et al 2011Sun et al , 2013 were used to calculate the Auger resonance energies and widths of K-shell excited states. Later, the K-shell Auger processes of O + -O 4+ were investigated by using the R-matrix method (Petrini 1981;Petrini & Da Silva 1996;Zeng et al 2001Zeng et al , 2004Zeng & Yuan 2002;Olalla et al 2002;Pradhan et al 2003;Garcia et al 2005), which represent the state-of-the-art ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%
“…( f ) Saddle-point complex-rotation method computation from Sun et al (2013). (g) R-matrix computation from Garcia et al (2005).…”
mentioning
confidence: 99%
“…In addition, some experimental lines of 1s2p 4 resonances in B-like ions from high-resolution Auger spectrum were observed by Bruch et al [3] and by Kádár et al [4]. On the theoretical side, calculations of Auger energies of the 1s 2p 4 ( 2 S, 2,4 P, 2 D) resonances in B-like ions have been performed using various ab initio methods such as the perturbation with super structure code (PSC) used by Safronova et al [5,6], the multiconfiguration Dirac-Fock (MCDF) approach employed by Chen and Crasemann [7], the unrestricted Hartree-Fock (UHF) self-consistent-field (SCF) method used by Bruch et al [3] and the saddle-point variation and SPCR technique utilized by Sun et al [8]. In the preceding experimental studies [1][2][3][4], various lines were not identified such as the not-identified O-like lines reported by Kádár et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some discrepancies in the above calculations [3,[5][6][7] are observed due mainly to strong electron correlation effects in B-like ions. The goal in the works of Sun et al [8] was to solve the preceding theoretical discrepancies and to identify some unknown experimental lines from 1s2p 4 resonances in B-Like C + , O 3+ and Ne 5+ ions. However, the high-relativistic calculations reported by Sun et al [8] have been limited to the 1s 2p 4 ( 2 S, 2,4 P, 2 D) resonances in B-like C + , O 3+ , Ne 5+ , Mg 7+ and Si 9+ ions.…”
Section: Introductionmentioning
confidence: 99%